Análisis de algoritmos de seguridad para el protocolo IEEE 802.16d (WIMAX-FIJO) - Arequipa Tayupanta, Alan David (2016)
This paper aims to analyze the security algorithms for the IEEE 802.16d protocol, transmitting different strings (from 6 bits to 32 bits), for this, a research scenario WIMAX (A base station, two receiver was simulated clients, a stranger to the network) agent in the OMNET software ++ through which, the implementation of algorithms AES (Advanced Encryption Standard) and DES (Standard data Encryption) to observe the protection afforded to information was made that transmitted and received. From the results obtained and analyzed, it was found that the matching ratio of DES protocol is higher with 5.67% against AES, which shows that it is vulnerable to find the size of the TEK of a String; on the other hand, the time of encryption and decryption algorithm is DES with significantly higher (88.34% / 89.42%) relative to AES, also it was verified that the security index of AES algorithm provides a 23.29 % compared to DES.